2014
DOI: 10.1007/s11418-013-0813-9
|View full text |Cite
|
Sign up to set email alerts
|

Wound healing activities of standardized pomegranate rind extract and its major antioxidant ellagic acid in rat dermal wounds

Abstract: The in vivo wound healing potential of a standardized pomegranate rind extract (SPRE) and its major antioxidant constituent, ellagic acid (EA, 13 %, w/w), were investigated in three rat dermal wound models. It was found that both SPRE (5 and 2.5 %) and its equivalent amount of EA (0.65 and 0.325 %) increased the tensile strength of the incision wound by a maximum of 35.43 and 31.82 %, respectively. SPRE at 5 and 2.5 % accelerated wound contraction of the excision wound and the burn wound, while EA was effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 26 publications
2
26
0
1
Order By: Relevance
“…Outcome of the study showed both rind extract and its equivalent amount of ellagic acid increased the tensile strength of the incision wound. 36 Pomegranate extract and urolithin-A decreased inflammation markers (iNOS, cycloxygenase-2, PTGES and PGE (2) in colonic mucosa) and modulated favorably the gut microbiota. 37 Other study finding revealed that pomegranate fruit extract inhibited the IL-1beta-induced proteoglycan breakdown in cartilage explants.…”
Section: Anti-inflammatory and Analgesic Effectmentioning
confidence: 90%
“…Outcome of the study showed both rind extract and its equivalent amount of ellagic acid increased the tensile strength of the incision wound. 36 Pomegranate extract and urolithin-A decreased inflammation markers (iNOS, cycloxygenase-2, PTGES and PGE (2) in colonic mucosa) and modulated favorably the gut microbiota. 37 Other study finding revealed that pomegranate fruit extract inhibited the IL-1beta-induced proteoglycan breakdown in cartilage explants.…”
Section: Anti-inflammatory and Analgesic Effectmentioning
confidence: 90%
“…Previously, a topical ointment prepared with polyethylene glycol and 5 % standardized pomegranate rind extract containing ellagic acid (13 %) was developed for release and skin permeation studies and was found to exhibit acceptable physicochemical properties [206]. When the wound healing activities of this ointment were compared with the equivalent amount of ellagic acid (0.65 %), the latter was less effective in inhibiting neutrophil infiltration and collagen augmentation in rat skin [207]. However, both products applied topically exhibited similar anti-inflammatory effects against a mouse model of contact dermatitis [92].…”
Section: Ellagic Acid and Skin Protectionmentioning
confidence: 99%
“…In all these cases, there was a clear increase in activity that prompted the various authors to propose that these modifications be employed to increase ellagic acidʼs therapeutic utility as an anticancer agent. In the case of skin protection, some authors proposed the use of nanoemulsions [205], ointment (polyethylene glycol) [92,206,207], or niosomes (Span 60-Tween 60, 2 : 1 and 15 % polyethylene glycol 400) [208]. Again, all these novel formulations led to clear advantages, such as access to the deeper skin layers [204] or better delivery of ellagic acid through human epidermis and dermis [208].…”
Section: Pharmacokinetic Properties Of Ellagic Acidmentioning
confidence: 99%
“…Bifidobacterium and Lactobacillus spices) [28,29] which when administered as probiotics are effective in the management of IBD [30,31]. The anti-nociceptive effect of the P. granatum extracts is also shown by a number of studies [32][33][34], though we did not observe significant effects for the herb on pain symptoms.…”
Section: A N U S C R I P Tmentioning
confidence: 48%